The Implementation of Mystery Box Learning Media in Teaching Procedural Texts for Grade X at MA Pesantren Al-Ghoits - Jasmine Noer Aini1; Mulia Putri Khasanah; Taswirul Afkar (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to examine the effectiveness of the Mystery Box teaching media in enhancing students' understanding of procedural texts in grade X at MA Pondok Pesantren Al-Ghoits. This innovative media is designed to create an interactive, enjoyable, and engaging learning environment. The research employs a qualitative approach with a classroom action research (CAR) design conducted in two cycles. Data were collected through observations, interviews, and learning outcome tests. The findings indicate that the implementation of the Mystery Box significantly improved student participation, accompanied by an increase in the average score of procedural text comprehension from the first to the second cycle. This media not only motivated students to actively engage in the learning process but also helped them grasp the material more effectively. Thus, the Mystery Box has proven to be an effective teaching tool to support the success of learning activities, particularly in procedural text material.